2022
DOI: 10.1007/s00167-021-06856-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, interpretation, and management of unexpected positive cultures in revision TKA: a systematic review

Abstract: PurposeUnexpected positive intraoperative cultures (UPIC) found in revision total knee arthroplasty (TKA) are difficult to interpret. Management goes along with risks for both over‐ and undertreating a potential periprosthetic joint infection (PJI). The objective of this systematic review was to determine the prevalence of UPIC in revision TKA surgery, evaluate the diagnostic workup process and the postoperative treatment, and assess outcome regarding re‐revision rates. MethodsEvidence was gathered from Medlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The criteria used to establish PJI as the main cause in patients undergoing rTKA are also relevant in defining the infection rates in this population of patients. A recent study showed that more than 8% of patients undergoing aseptic rTKA had positive intraoperative cultures [ 50 ]. This finding shows that the ratio of infection in implant failures may be higher than considered in many studies and, at the same time, represents a challenge for the orthopedic surgeon in the management of these cases, as the decision to treat these patients or not may influence the rates of revision and implant survival [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria used to establish PJI as the main cause in patients undergoing rTKA are also relevant in defining the infection rates in this population of patients. A recent study showed that more than 8% of patients undergoing aseptic rTKA had positive intraoperative cultures [ 50 ]. This finding shows that the ratio of infection in implant failures may be higher than considered in many studies and, at the same time, represents a challenge for the orthopedic surgeon in the management of these cases, as the decision to treat these patients or not may influence the rates of revision and implant survival [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that more than 8% of patients undergoing aseptic rTKA had positive intraoperative cultures [ 50 ]. This finding shows that the ratio of infection in implant failures may be higher than considered in many studies and, at the same time, represents a challenge for the orthopedic surgeon in the management of these cases, as the decision to treat these patients or not may influence the rates of revision and implant survival [ 50 ]. Moreover, new and advanced alternative methods for diagnosing infection can help correctly classify the reason for revision as PJI and not aseptic loosening; therefore, a shift in the results of recent studies subsequently reporting higher rates of PJI may be expected [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is no clear consensus on how to handle UPICs and UNICs [16, 22, 23, 28]. Over‐ as well as undertreatment of patients with UPICs and UNICs may affect morbidity, mortality, implant survival and subsequent re‐revision rates [16, 28].…”
Section: Introductionmentioning
confidence: 99%
“…These unexpected negative intraoperative cultures (UNIC) in clear infections can occur between 5 and 41% of the cases [3, 14]. In contrast, in 8.3–12.0% of presumed aseptic revisions, unexpected positive intraoperative culture/s (UPIC) can occur [10, 16, 26]. There is conflicting evidence on the clinical relevance of UPICs, which are often low‐virulent microorganisms [13, 26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation